Relative age effect presence among swimmers within Youth Olympic Games - Cular, D.; Granic, I.; Babic, M. (Acta Kinesiologica, 2023)
Purpose: This study investigates the presence of relative age effects (RAE) in swimming at the Youth Olympic Games (YOG), the highest international-level competition for young swimmers. Methods: Data from 980 participants who competed in swimming at the 2018 YOG were analyzed. Chi-square tests were used to assess RAE distribution by dividing the participants into sub-groups based on their birth year. Descriptive statistics were employed to examine the unequal distribution of athletes across different birth years. Results: The Chi-square test revealed a significant difference in the distribution of athletes across the birth years (X² = 289.869, p < 0.001). The analysis demonstrated an overrepresentation of the oldest subgroups (born in 2000 and 2001) and an underrepresentation of the youngest subgroup (born in 2003). These findings indicate a clear relative age effect within swimming at the YOG, highlighting a bias in talent selection and success. Conclusions: The study underscores the importance of addressing relative age effects in swimming to ensure fairness in talent identification and development. To mitigate RAE, it is recommended to revise age grouping in competitions by considering smaller age ranges and moving away from a calendar year cut-off system. Furthermore, implementing corrective adjustments for swimming times based on chronological decimal age can assist coaches in evaluating talent within their teams and clubs. By addressing relative age effects, sports organizations and coaches can create equal opportunities for all swimmers, irrespective of their birthdate, fostering a more equitable and inclusive environment for young athletes. Future studies should explore RAE in other sports, specific disciplines, genders and develop targeted methodology for comparing fairness of competition systems within different sports. By implementing such strategies, sports organizations and coaches can maximize the potential of young athlets and ensure a fairtalent identification and development process for all participants.